Chemical geodynamics of mafic magmatism above subduction zones - Zheng, Yong-Fei; Xu, Zheng; Chen, Long; Dai, Li-Qun; Zhao, Zi-Fu (Journal of Asian earth sciences, 2020)
•Mafic magmatism above oceanic and continental subduction zones proceeds in two-stage processes.•Crustal signatures are transferred by liquid phases into the mantle source of mafic igneous rocks.•The fractionation of melt-mobile trace elements is significant at the slab-mantle interface.•Metasomatism is the physicochemical mechanism for the geochemical transfer in subduction zones.•The melting of rocks is dictated by the thermal structure of subduction zones at different depths. The geochemical signatures of subducting crust have been identified in various types of mafic igneous rocks at convergent plate boundaries, where island arc basalts (IAB) and continental arc andesite are accepted as the typical products of subduction zone magmatism. These crustal signatures are commonly represented not only by enrichment in large ion lithophile elements (LILE) and light rare earth elements (LREE) relative to normal mid-ocean ridge basalts (MORB), but also by enrichment in radiogenic Sr isotopes but depletion in radiogenic Nd isotopes relative to the primitive mantle. Such enriched signatures also occur in oceanic island basalts (OIB) and their continental counterparts, but their origin has been controversial in igneous petrology. The present review focuses on the origin of enriched signatures in mafic igneous rocks above subduction zones. Although these mafic rocks are distributed in both interplate and intraplate areas, they are generally categorized into two series according to their trace element distribution patterns in the primitive mantle-normalized diagram. One is IAB-like series, showing enrichment in LILE, Pb and LREE but depletion in high field strength elements (HFSE) such as Nb and Ta relative to heavy rare earth elements (HREE). The other is OIB-like series, exhibiting enrichment in LILE and LREE, enrichment or non-depletion in HFSE but depletion in Pb relative to HREE. In either series, these mafic igneous rocks show enhanced enrichment of LILE and LREE with increasing their incompatibility relative to normal MORB, indicating the presence of crustal materials in these mafic igneous rocks. Inspection of the mass balance in major and trace elements between source and product indicates that subducting crustal rocks were not directly incorporated into the mantle sources of both series. Instead, they underwent metamorphic dehydration and partial melting at different depths to produce liquid phases, which dominate the budget of fluid- to melt-mobile elements and their pertinent radiogenic isotopes in the mantle sources. As a consequence, the composition of liquid phases is a key to the geochemical composition of both series. Therefore, the crustal materials are transferred by the liquid phases via metasomatic reactions into the mantle sources at the slab-mantle interface in subduction channels. As such, the difference in the geochemical transfer from the subducting crust into the mantle can account for the difference in the composition between the interplate IAB-like and intraplate OIB-like series. This provides a holistic model for the origin of both IAB- and OIB-like series mafic igneous rocks above subduction zones.